Revisão taxonômica do grupo de espécies de Mischocyttarus (Omega) filiformis (de Saussure, 1854) (Hymenoptera: Vespidae, Polistinae) - BORGES, Rafael Cabral (Universidade Federal do Pará, 2017)
Mischocyttarus de Saussure is the only genus in the Mischocyttarini tribe. This tribe is composed by approximately 250 species, being this genus the largest among the Polistinae. M. filiformis (de Saussure) is the type species in the subgenus Omega, and was described based only in the type specimen from Pará state (Brazil). Three related species, posteriorly described, compose the M. filiformis species-group: M. buyssoni (Ducke), M. napoensis Richards e M. omicron Richards. This work aimed to perform a taxonomic revision of the Mischocyttarus filiformis species group based on the analisis of external morphology traits from the type specimens of the previously described species, and in additional specimens from collections in Brazil and in other countries. Four species were redescribed in this study, M. filiformis, M. buyssoni, M. napoensis e M. omicron, and six new species were described, Mischocyttarus sp. nov 1, Mischocyttarus sp. nov 2, Mischocyttarus sp. nov 3, Mischocyttarus sp. nov 4, Mischocyttarus sp. nov 5, Mischocyttarus sp. nov 6, thus increasing to 10 the number of species in this species-group. The geographic distributional records of the species M. filiformis, M. buyssoni e M. omicron is here extended. The male of M. filiformis is described. The nests of M. filiformis, M. buyssoni, Mischocyttarus sp. nov 3, Mischocyttarus sp. nov 4, Mischocyttarus sp. nov 5 are described and additional information about the paralectotypes of M. buyssoni deposited in the MPEG collection is provided.